Acinetobacter baumannii bloodstream infections in a tertiary hospital: Antimicrobial resistance surveillance - Al-Mously, Najwa (International Journal of Infection Control, 2013)
Background: Nosocomial bacteremia caused by Acinetobacter baumannii (AB) is of increasing concern in critically ill patients. There is a world-wide increase in the emergence of multidrug-resistant (MDR) AB to antimicrobials. Therefore we conducted this study to evaluate the resistance pattern of AB in patients with bacteremia. Methods: This is a retrospective study conducted in a tertiary hospital in Saudi Arabia. During the period from April 2008 till April 2010, data for AB isolated from blood were collected. Multidrug resistant AB was defined as resistance to three or more classes of antibiotics. Results: 191 isolates of AB were recovered from blood. The majority of cases were reported in surgical ICU (40.8%). The highest resistance rates to antimicrobials were reported for cefepime (73.8%) and piperacillin / tazobactam (72.3%), followed by ciprofloxacin (68%), and gentamicin (66%). Resistance rates were also high to imipenem (61.3%) and meropenem (60.7%). Low rates of resistance to colistin (0.5%) and to tigecycline (3.9%) were observed. 132 (69%) AB isolates were MDR and 104 (78.8%) of these MDR strains showed sensitivity only to colistin and tigecycline. Conclusion: Bacteremia due to AB was the highest in surgical ICU. The emergence of MDR AB is increasing and the resistance rates to carbapenems are alarming. Urgent measures are needed to slow development of MDR AB. We recommend encouraging clinicians for strict adherence to infection control policies, enhancement of ongoing antimicrobial stewardship program and restrictive use of recommended antibiotics according to susceptibility testing and local guidelines. In-house surveillance is needed for the detection of resistance rates particularly MDR AB.